2020
DOI: 10.3390/ani10020185
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fermented Tea Residue on Fattening Performance, Meat Quality, Digestive Performance, Serum Antioxidant Capacity, and Intestinal Morphology in Fatteners

Abstract: This study investigated the dietary supplementation of tea residue fermented by Bacillus subtilis, Aspergillus niger, and Saccharomyces cerevisiae, to explore its effects on growth performance, digestion performance, meat quality, serum antioxidant capacity, and intestinal morphology in pigs bred for rapid growth, also known as fatteners. One hundred and ninety-two healthy “Duroc × Landrace × Yorkshire” ternary hybrid pigs (body weight 70 ± 1.0 kg) were randomly divided into four groups according to the feedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 35 publications
(37 reference statements)
3
34
0
Order By: Relevance
“…The ratio of villus height to crypt depth can reflect the function of the small intestine. Decreased ratios indicate damage to the mucosa, reduced digestion and absorption and are often accompanied by diarrhea and growth retardation ( Ding et al., 2020 ). Our research showed that dietary PS supplementation improved the immune function of the intestines, contributing to better intestinal health status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ratio of villus height to crypt depth can reflect the function of the small intestine. Decreased ratios indicate damage to the mucosa, reduced digestion and absorption and are often accompanied by diarrhea and growth retardation ( Ding et al., 2020 ). Our research showed that dietary PS supplementation improved the immune function of the intestines, contributing to better intestinal health status.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that muscle pH, meat color, water, and tenderness can comprehensively reflect meat quality ( Ding et al., 2020 ). A low pH is related to the accumulation of lactic acid caused by anaerobic respiration, which may affect water retention capacity ( Qi et al., 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, pigs fed with FCF had higher ALP, GLU, IgG, IgM, SOD, and T-AOC levels compared with pigs that received basal feed, which demonstrated that FCF has benefit for animal growth, nutrition absorption, and animal health. Similar results have been obtained in other studies using fermented feed (39)(40)(41). Health benefit effects of FCF may be related to probiotics contained in fermented feed.…”
Section: Discussionsupporting
confidence: 90%
“…Villous height is regarded as a sign of surface area of nutrient absorption, and crypt depth can reflect the epithelial cell proliferation, which could be deeper if there is higher epithelial cell turnover [ 21 ]. Late gestation is the rapid development period for fetal intestine [ 22 ].…”
Section: Discussionmentioning
confidence: 99%